A Review of the Implementation of Sustainable Plastic Waste Management - Beatriks Liku Gustiawati; Herdis Herdiansyah; Evi Frimawaty (International Journal of Science and Society, 2023)
Since the Chinese government prohibited the import of plastic waste, it has encouraged the Japanese government to increase the domestic processing of plastic waste. In 2018, among the highest rates worldwide, Japan successfully recycled up to 84 percent of all plastic collected. Although some efforts have been made by the Indonesian government to collect plastics, the overall performance of plastic recycling is unknown due to the failure to integrate informal sector recycling actors’ activities with the government and community activities in the formal sector. This limited information on the generation and management of plastic waste is a gap that needs to be addressed. This study was conducted using a qualitative descriptive method through an article review. The article review was conducted on several scientific articles on post-consumer plastic waste management policies in Japan and Indonesia. In general, plastic recycling activities in Japan are more formalized in terms of collecting and recycling through a special organization founded by the Japanese government, namely the Japan Containers and Packaging Recycling Association (JCPRA). The JCPRA helps the Japanese government to provide more detailed documented data on policy development and technical management of plastic waste. One that can be applied by Indonesia is to form an organization similar to JCPRA in Japan to become an operator in managing the plastic materials flow and plastic waste recycling in Indonesia so that Indonesia can provide valid information on plastic waste generation and management to develop plastic waste management strategies to control plastic waste pollution in the environment.